Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Karyawan pada PT. BPR Syariah Adeco Langsa (Studi Kasus : PT. BPR Syariah Adeco di Langsa) - Safwani Safwani; Suryani Suryani (Institut Agama Islam Negeri Padangsidimpuan, 2020)
This study aimed to examine the influence of leadership style and organizational culiture on the performance of employess of PT. BPR Syariah Adeco in Langsa. The population used is all employees of PT.BPR Syariah Adeco Langsa, amouting to 30 people, with the census method. Data Analysis in this study used validity, reliability, classic assumption tests, multiple linear regression analysis, coefficient of determination and hypothesis testing with IBM SPSS program analysis tools. The results of research and discussion explain that there is a sugnificant influence between leadership style on employee performance. Organizational culture variables significantly influence employee performance. The significant influence between leadership style variables and organizational cultulre together/simultaneously on employee performance, which is indicated by the coefficient of determination with a result of 61.0%. while the rest of the 3.9% employee performance variables can be explained from other variables not included in this study. Keywords: Leadership style, organizational culture and employee performance